n-Alkanes and phenols in bottom sediments and brown algae from the Blake-Bahama Abyssal Plain - Valery I Peresypkin; Evgeny A Romankevich; Nikolay A Belyaev (PANGAEA, 2003)
Using gas chromatography technique we examined molecular composition of n-alkanes and lignin from bottom sediments of a core 385 cm long collected in the region of the Blake-Bahama Abyssal Plain. We determined C_org concentrations and lignin composition in soils, mangrove roots and leaves, in algae Sargassum and Ascophyllum, in corals and timber of a sunken ship; they were compared with data on lignin in bottom sediments. Mixed planktonogenic and terrigenous origin of organic matter in the core was proved with different proportions of terrigenous and planktonogenic components at different levels. Multiple changes in dominating sources of organic matter over a period required for accumulation of a four meter thick sedimentary sequence (about 4 m) are shown as obtained from changes in composition and contents of organic-chemical markers referring to classes of n-alkanes and phenols.
Supplement to: Peresypkin, VI et al. (2003): Paraffine hydrocarbons and lignin in the bottom sediments of Blake-Bahama Abyssal Plain. Translated from Okeanologiya, 2003, 43(4), 535-542, Oceanology, 43(4), 503-511